Cultural Monopoly Game: Designing and Testing Game-Based Media for Intangible Cultural Heritage Learning in Elementary School - Puspitasari, Dina Sri; Ary, Deasylina da (Jurnal Pendidikan Progresif, 2024)
Development of Cultural Monopoly Learning in Intangibel Cultural Heritage Materials Elementary School. Objectives: The ineffective use of learning media and low student learning outcomes are one of the problems found at Kedungjenar Elementary School. This study was conducted with the aim of developing, testing the feasibility, and testing the effectiveness of game-based media, namely cultural monopoly with the material of intangible cultural heritage in the fifth grade.  Methods: he research method used in this research is R&D (Reasearch and Development) with research design by Borg and Gall. Data collection techniques using tests (pretest and posttest), with non-test techniques (observation, interviews, questionnaires, and documentation). Findings: The results showed that the media was feasible to use based on the percentage of assessments from media experts and material experts of 90,15% with a very feasible category. The analysis technique used normality test, t-test, and n-gain test. The results of the data normality test showed a sig value. > 0,05 so that the data is normally distributed. The t-test results obtained 19,270 with sig. <0,05 indicates that there is an increase in learning outcomes before and after using cultural monopoly media. While the results of the N-Gain test obtained an increase in learning outcomes of 0,6498 with moderate criteria. Conclusion: With an increase in the average, it can be concluded that the cultural monopoly learning media on intangible cultural heritage material is effectively used in fifth grade elementary school. Keywords: learning media, monopoly game, intangible culture.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024126